EXPLORING THE REALIZATION OF COHESION AS A RESOURCE OF TEXT TEXTURE ON UNDERGRADUATE STUDENTS’ ACADEMIC WRITING - Ngongo, Magdalena; Ndandara, Alfriani (English Review: Journal of English Education, 2024)
This study aimed to explore the realization of cohesion as  text texture resource on undergraduate students’ academic writing. The researchers were aware that students’ writing might be affected by their understanding of what had been learned before. To write an academic writing was not easy for them since they should integrate knowledge either the content being writing or grammar including text texture. Texture of text were realized in cohesion devices namely reference, conjunction, ellipsis and lexical organization. In order to do this study, the researchers applied qualitative method, the population was  academic writings texts that were written by students in 2021. Purposive random sampling strategy were applied to get the 12 samples of theses writing specified only texts related to teaching and learning English. Data gained were identified and classified based on the view of resources of cohesion realization and then be analyzed and interpreted to get its result about the text texture. Based on the analysis it was found out that the realization of cohesion as resources of text texture were in reference that covered to personal, demonstrative and comparative references; conjunctions, ellipsis, substitution and lexical organization It was found out that cohesion resources were realized in reference, conjunction and repetition were mostly used. This fact might because of text types and students’ limitation of using varieties realization of substitution, ellipsis and other lexical cohesion. It is hoped that the result of this study can give contribution to the English lecturers, especially to the lecturers of writing and  grammar.